VALORISATION DES EAUX EPUREES DANS LE DOMAINE AGRICOLE (SOUK AHRAS) - AMEL GUETTAR; MARWA REHAILI (My University, 2023)
Water is a vital source for all living beings, but unfortunately the problem of pollution presents one of the mostworrying aspects of the degradation of naturalenvironments, that'swhy the elimination of pollutantsfrom water has becomecompulsory The objective of thisworkconsists in characterizing the physico- chemicalquality and evaluating the degree of organic pollution of the waters of the area. study. In ourworkweproceeded to the research of the revealing and determiningparameters of the organic pollution present in the medium to bestudied (temperature, pH, electricalconductivity, suspendedmatter, dry residue, dissolvedoxygen, BOD5, COD, copper, nitrites, nitrates and sulphate) for a period of twomonths. The representative assessment of the concentrations revealedremarkable contamination of the water due to a significant presence of organicload. ------------------------------------------------------------------------------- تعد المياه مصدرا حيويا لجميع الكائنات الحية،ولك للأسف ،تمثل مشكلة التلوث حد الجوانب الأكثر إثارة للقلق في تدهور البيئة ، و لهطا أصبح التخلص من الملوثات من المياه أمرا الزاميا . و الهدف من هذا العمل هو توصيف الجودة الفيزيائية و الكيميائية و تقييم درجة التلوث العضوي لمياه المنطقة المدروسة (سدراته). في عملنا ،شرعنا في البحث عن معاملات الكشف و تحديد التلوث العضوي في الوسط المراد دراسته (درجة حرارة، درجة حموضة ، التوصيل الكهربائي ،البقايا الجافة ، الأكسجين المذاب، النحاس ، النيتريت ، النترات، و الكبريت لمدة شهرين . ) لمدة DCO، DBO5 أظهر التقييم التمثيلي للتركيزات تلوثا ملحوظا للمياه بسبب الوجود الكبير للعناصر العضوية . ------------------------------------------------------------------------------- L’eau est une source vitale pour tous les êtres vivants ,mais malheureusement le problème de la pollution présente un des aspects les plus inquiétant de la dégradation des milieux naturel , c’est pourquoi l’élimination des polluants de l’eau est devenu obligatoire . L'objectif de ce travail consiste à caractériser la qualité physico-chimique et à évaluer le degré de pollution organique des eaux de la zone )sedrata ). Dans notre travail nous avons procédé à la recherche des paramètres révélateurs et déterminants de la pollution organique présente dans le milieu à étudier (température, pH, conductivité électrique, matières en suspension, résidu sec, oxygène dissous, DBO5, DCO, cuivre, nitrites, nitrates et sulfate) pendant une période de deux mois. L'évaluation représentative des concentrations a révélé une contamination remarquable de l'eau due à une présence importante de charge organique.